The effects of polarization dynamics and domain switching energies on field induced phase transformations of perovskite ferroelectrics - Franzbach, Daniel J.; Xu, Bai-Xiang; Mueller, Ralf; Webber, Kyle Grant (Applied Physics Letters, 2011)
A time-dependent phase field model was utilized to investigate the electric field induced tetragonal-to-orthorhombic (T -> O) planar phase transformations of perovskite materials, indicated by the simulated semi-discontinuous polarization-electric field hysteresis. Simulations show that transformations are sensitive to the crystallographic orientation of the applied electric field, the energy threshold for 90 degrees domain switching and the rotation path between tetragonal variants. This indicates that the field induced phase transformation behavior has a significant influence on the evaluation and validation of the Landau coefficients. (C) 2011 American Institute of Physics. [doi:10.1063/1.3644957]
Keywords: dielectric hysteresis; dielectric polarisation; electric domains; ferroelectric materials; ferroelectric switching; ferroelectric transitions; relaxor ferroelectrics